2008
DOI: 10.1111/j.1445-5994.2007.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with heart failure appropriately undergo invasive procedures post‐myocardial infarction? Results from a prospective multicentre study

Abstract: The presence of CHF post-MI resulted in lower rates of use of angiography and angioplasty, which was not explained by lower procedure rates in the elderly. As these guideline-recommended procedures may improve survival in patients with CHF post-MI, future strategies should aim to enhance their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In registry studies of fibrinolytic-treated patients from Western Europe, high rates of in-hospital angiography and PCI are reported 11. Also a recent 20-centre Australian survey showed that after STEMI, 87% of patients underwent in-hospital angiography, with 65% having PCI 37. The WEST (Which Early ST elevation myocardial infarction Therapy) trial supports an approach of urgent, but non-immediate, post-fibrinolytic PCI 38.…”
Section: Timing Of Non-emergency Angiography and Interventionmentioning
confidence: 99%
“…In registry studies of fibrinolytic-treated patients from Western Europe, high rates of in-hospital angiography and PCI are reported 11. Also a recent 20-centre Australian survey showed that after STEMI, 87% of patients underwent in-hospital angiography, with 65% having PCI 37. The WEST (Which Early ST elevation myocardial infarction Therapy) trial supports an approach of urgent, but non-immediate, post-fibrinolytic PCI 38.…”
Section: Timing Of Non-emergency Angiography and Interventionmentioning
confidence: 99%